Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Kim, Jong Hee; Park, Jeong-In; Kim, Yewon; Park, Mira; Kim, Jang Kyun; Han, Young-Seok; Kim, Youn-Jung (Ocean science journal, 2025)
Okadaic acid (OA) is a marine toxin generated by dinoflagellates, which poses considerable health risks to humans, primarily by causing diarrhetic shellfish poisoning via the consumption of contaminated bivalve mollusks. In this research, we examined the cytotoxic impact of OA on the EA.hy926 human vascular endothelial cell line and accordingly observed dose-dependent inhibition of cell viability upon exposure to OA using MTT assays. Transcriptomic analysis based on RNA sequencing revealed significant differential gene expressions associated with disrupted cell growth, proliferation, DNA damage response, angiogenesis, and DNA replication via GO and KEGG pathway enrichment analyses. In conjunction with the findings of ingenuity pathway analysis, the activation of inflammatory pathways, including the osteoarthritis and cachexia signaling pathways, is highlighted. Further validation via RT-qPCR analysis confirmed the upregulation of CDKN2D, CDKN1A, SOD2, SIRT1, and PLK1, which may be induced by inflammatory response and inhibition of DNA damage repair mechanisms. In addition, flow cytometric analysis also confirmed that OA accelerated the G1/S transition of vascular endothelial cells. OA has a significant impact on the vascular endothelium, and this study contributes to a broader understanding of the potential toxic effects of OA on cellular response mechanisms to OA.